Gritty leaders promoting employees’ thriving at work - Rego, A.; Cavazotte, F.; Cunha, M. P. e.; Valverde, C.; Meyer, M.; Giustiniano, L. (Journal of Management, 2021)
Four studies (a vignette-based experiment conducted in Portugal and Brazil, a two-wave multisource field study in Portugal, a three-wave field study in the United States, and a multisource field study in Portugal), in which conscientiousness, a “rival” of grit, was controlled for, provide theoretical and empirical evidence for a model testing what (e.g., grit in leaders), why (e.g., employee self-attributed grit), and when (e.g., leader support) grit supports thriving at work. First, gritty employees are more likely to thrive. Second, conveyed leader grit (i.e., grit as perceived by employees) predicts employee grit. Third, conveyed leader grit and leader self-attributed grit are conceptually different, and although the two relate positively with employee self-attributed grit, the former is a better predictor of employee self-attributed grit. Fourth, leader support operates as a boundary condition, in that the indirect association of conveyed leader grit with employee thriving is stronger when the leader is perceived as supportive. Our research also indicates that the concept of grit is more textured than habitually considered and that more attention must be paid to the boundary conditions of its development and impact.